A review of the applications of nanofluids in solar energy - Mahian, Omid; Kianifar, Ali; Kalogirou, Soteris A.; Pop, Ioan M.; Wongwises, Somchai (My University, 2013)
Utilizing nanofluids as an advanced kind of liquid mixture with a small concentration of nanometer-sized solid particles in suspension is a relatively new field, which is less than two decades old. The aim of this review paper is the investigation of the nanofluids' applications in solar thermal engineering systems. The shortage of fossil fuels and environmental considerations motivated the researchers to use alternative energy sources such as solar energy. Therefore, it is essential to enhance the efficiency and performance of the solar thermal systems. Nearly all of the former works conducted on the applications of nanofluids in solar energy is regarding their applications in collectors and solar water heaters. Therefore, a major part of this review paper allocated to the effects of nanofluids on the performance of solar collectors and solar water heaters from the efficiency, economic and environmental considerations viewpoints. In addition, some reported works on the applications of nanofluids in thermal energy storage, solar cells, and solar stills are reviewed. Subsequently, some suggestions are made to use the nanofluids in different solar thermal systems such as photovoltaic/thermal systems, solar ponds, solar thermoelectric cells, and so on. Finally, the challenges of using nanofluids in solar energy devices are discussed.
Keywords: Challenges; Economic and environmental considerations; Efficiency; Nanofluids; Solar energy